Arabidopsis thaliana is a susceptible host plant for the holoparasite Cuscuta spec - Sauer, Norbert; et al. (Planta, 2007)
Arabidopsis thaliana and Cuscuta spec. represent a compatible host-parasite combination. Cuscuta produces a haustorium that penetrates the host tissue. In early stages of development the searching hyphae on the tip of the haustorial cone are connected to the host tissue by interspecific plasmodesmata. Ten days after infection, translocation of the fluorescent dyes, Texas Red (TR) and 5,6-carboxyfluorescein (CF), demonstrates the existence of a continuous connection between xylem and phloem of the host and parasite. Cuscuta becomes the dominant sink in this host-parasite system. Transgenic Arabidopsis plants expressing genes encoding the green fluorescent protein (GFP; 27 kDa) or a GFP-ubiquitin fusion (36 kDa), respectively, under the companion cell (CC)-specific AtSUC2 promoter were used to monitor the transfer of these proteins from the host sieve elements to those of Cuscuta. Although GFP is transferred unimpedly to the parasite, the GFP-ubiquitin fusion could not be detected in Cuscuta. A translocation of the GFP-ubiquitin fusion protein was found to be restricted to the phloem of the host, although a functional symplastic pathway exists between the host and parasite, as demonstrated by the transport of CF. These results indicate a peripheral size exclusion limit (SEL) between 27 and 36 kDa for the symplastic connections between host and Cuscuta sieve elements. Forty-six accessions of A. thaliana covering the entire range of its genetic diversity, as well as Arabidopsis halleri, were found to be susceptible towards Cuscuta reflexa. © 2007 Springer-Verlag.
Keywords: Arabidopsis; Carboxyfluorescein; Cuscuta; GFP-ubiquitin; Green fluorescent protein (GFP); Symplastic